Are Explicit Apologies Proportional to the Offenses They Address?. Issue 1 (2nd January 2016) - Heritage, John; Raymond, Chase Wesley
Abstract : We consider here Goffman's proposal of proportionality between virtual offenses and remedial actions, based on the examination of 102 cases of explicit apologies. To this end, we offer a typology of the primary apology formats within the dataset, together with a broad categorization of the types of virtual offenses to which these apologies are addressed. We find a broad proportionality between apologies and the offenses they remediate when the offenses to be remediated are minor; however, this relationship is not sustained among larger apologies and offenses. In the latter cases, relational and contextual contingencies are important intervening factors influencing apology construction.